Analisis Kinerja Keuangan Daerah Ditinjau dari Efisiensi dan Pertumbuhan Belanja pada Pemerintah Kota Ambon Tahun Anggaran 2022–2024 - Pattimahu, Angel Merlyn; Tangke, Diar Muzna (ISAS, 2025)
Regional governments have greater authority in managing their budget revenues and expenditures. Regional expenditure represents an obligation recognized as a deduction from net assets within a fiscal year. These funds are allocated to support the implementation of governmental functions at the provincial and municipal levels. This study aims to assess the efficiency level and expenditure growth of the Ambon City Government. The research employs a descriptive method with a focus on the Regional Financial and Asset Management Agency of Ambon City. Based on the analysis of expenditure efficiency ratios, the results show that efficiency fluctuated over the study period: 92.66% in 2022, increasing to 99.53% in 2023, and declining again to 86.63% in 2024. Meanwhile, expenditure growth also showed an unstable pattern, with –2.58% in 2022, rising to 7.26% in 2023, and decreasing again to –7.01% in 2024. These findings indicate dynamic fiscal management influenced by development priorities and the government’s fiscal capacity. Overall, the study highlights the importance of effective and consistent budget planning to maintain efficiency and support the achievement of regional development goals. Keywords: Local Government Expenditure, Efficiency, Assets, Budget, Expenditure Growth